2016
DOI: 10.1111/jedm.12107
|View full text |Cite
|
Sign up to set email alerts
|

Using Networks to Visualize and Analyze Process Data for Educational Assessment

Abstract: New technology enables interactive and adaptive scenario-based tasks (SBTs) to be adopted in educational measurement. At the same time, it is a challenging problem to build appropriate psychometric models to analyze data collected from these tasks, due to the complexity of the data. This study focuses on process data collected from SBTs. We explore the potential of using concepts and methods from social network analysis to represent and analyze process data. Empirical data were collected from the assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 20 publications
0
53
3
Order By: Relevance
“…Other studies applied SNA methods to understand the structures and features of non-human networks. For instance, researchers analyzed the networks of AOI (Areas of Interest) using data collected via tracking students' eyeball movements while answering science items in an onlinedelivered assessment [21]; and the transition networks of activities using action-log data recorded while students worked on complex online-delivered items [22]. In this study, we explore the usefulness of SNA in engineering education, specifically in terms of how SNA can assist in forming a deeper understanding of the communication processes and connections among EPSs evidenced through student-group discussions, for which information can be used as feedback to improve teaching and learning practices.…”
Section: Social Network Analysis and Education Researchmentioning
confidence: 99%
“…Other studies applied SNA methods to understand the structures and features of non-human networks. For instance, researchers analyzed the networks of AOI (Areas of Interest) using data collected via tracking students' eyeball movements while answering science items in an onlinedelivered assessment [21]; and the transition networks of activities using action-log data recorded while students worked on complex online-delivered items [22]. In this study, we explore the usefulness of SNA in engineering education, specifically in terms of how SNA can assist in forming a deeper understanding of the communication processes and connections among EPSs evidenced through student-group discussions, for which information can be used as feedback to improve teaching and learning practices.…”
Section: Social Network Analysis and Education Researchmentioning
confidence: 99%
“…In addition to connections among students, researchers have also used SNA to model the interactions among teachers, teaching coaches, and administrators to understand, for example, the impacts of interventions on school systems (Sweet, Thomas, & Junker, ). SNA has also been used to model nonhuman systems in education, such as the transitions among student activities recorded in the log data for simulation‐based assessment (Zhu, Shu, & von Davier, ) and students' eye movements while they were solving mathematics problems in scenario‐based assessment (Zhu & Feng, ). In both studies, network statistics were found to be closely related to student performance.…”
Section: Related Workmentioning
confidence: 99%
“…To take the temporal information into account, hierarchical vectorization of the rank ordered time intervals and the time interval distribution of event pairs were also introduced. In addition to these common analytic techniques, other existing data analytic methods for process data are Social Network Analysis (SNA; Zhu et al, 2016 ), Bayesian Networks/Bayes nets (BNs; Levy, 2014 ), Hidden Markov Model (Jeong et al, 2010 ), Markov Item Response Theory (Shu et al, 2017 ), diagraphs (DiCerbo et al, 2011 ) and process mining (Howard et al, 2010 ). Further, modern data mining techniques, including cluster analysis, decision trees, and artificial neural networks, have been used to reveal useful information about students' problem-solving strategies in various technology-enhanced assessments (e.g., Soller and Stevens, 2007 ; Kerr et al, 2011 ; Gobert et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%